BIMBINGAN KELOMPOK TEKNIK MODELING SIMBOLIS BERMUATAN KESENIAN TUNDANG EFEKTIF MENINGKATKAN HARMONI SOSIAL - Halida, Halida (Jurnal Kajian Pembelajaran dan Keilmuan, 2023)
This study aims to determine the effectiveness of group guidance with symbolic modeling techniques containing tundang art to improve students' social harmony. The research design used a pure experiment with a one-group model with pre-test and post-test. The research subjects were 102 junior high school class VII students in Pontianak. The instrument used is a social harmony scale of 45 items, the same instrument before and after treatment. The data used is interval data, the analysis is done through parametric statistics. Data analysis includes descriptive analysis and hypothesis testing using paired sample t-test. The results of the study revealed that group guidance with symbolic modeling techniques containing tundang art was effective in improving students' social harmony. The composition of Malay rhymes contained in tundang art is able to influence students' social harmony so that there is a change in the way of thinking and behaving in response to the stimulus. The conclusion of this study is that group guidance with symbolic modeling techniques containing tundang art is effective in improving students' social harmony